Wymagalność roszczenia o zapłatę kary umownej jako przesłanka dopuszczalności potrącenia. Uwagi z perspektywy historyka prawa - Sobczyk, Marek (PRAWO i WIĘŹ, 2024)
In this paper, I address the problem of the enforceability of a claim for payment of a contractual penalty in the context of the admissibility of the set-off of such a claim. This problem manifests itself primarily in a situation where the contractual provision regarding the penalty does not contain a deadline for its payment. The prevailing view in contemporary Polish case law is that in such a situation the obligation to pay the contractual penalty is indefinite, and therefore the claim for payment becomes due after the debtor is called upon to perform this obligation, which means that the creditor should first demand the payment of the contractual penalty. I tackle the issue from a historical perspective, starting from Roman law, through the ius commune and views expressed in legal science on the basis of the Code of Obligations of 1933, up to the modern academic and jurisprudential concepts. These concepts, to the extent that they emphasize the need for prior a demand for payment of a contractual penalty, establish a new requirement that braks with the old tradition of understanding of the enforceability of a claim for payment of a contractual penalty.